Implementation Of L-System In Procedural City Generation Using Java - Surya Sujarwo; William Salim; Ferry Yuwono (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Article discusses about the design and implementation of procedural content generation using java, especially the generation of virtual city. It is applied by using L-System to generate the elements of the city and also using some images as the base models. This method is proven to be more effective because it can produce almost unlimited variations of city in short amount of time without any needs to modify the application. The result of this application is a road map which can be used in many areas such as virtual reality, games, or other related purposes.